Tamizaje Conductual en adolescentes tempranos, Ibarra 2017: Teenage behavior screening, Ibarra 2017 (La U Investiga, 2019)
To detect potential behavioral disorders at emotional area, feeding habits and alcohol consumption in a group of early adolescents in the city of Ibarra, was the objective, through the characterization of the sociodemographic conditions and by applying of behavioral screening instruments, recommended by the Ministry of Public Health. A quantitative, non-experimental, descriptive and cross-sectional study was carriedout where the APGAR family tests, alcoholism screening, PHQ-2 depression, and feeding behavior screening were applied to 35 early adolescents (between 10 to 14 years of age) without any type of disability, arbitrarily selected in the city of Ibarra; descriptive statistics and Excel as data processor, were used to analyze results.The ethnic identification was mostly mestizo 86%, heterosexual in the totality, 5% presented a severe dysfunctional family APGAR, 3% had risky alcohol consumption, 71% presence of disorder in feeding behavior and 43% with depressed mood. The tests used alert us to potential problems and / or risk factors with a high sensitivity, but low specificity, which is why they are not definitive diagnostic criteria, but an earlydetection of high risk adolescents that warrants deeper assessment and intervention. The main disorders found in early adolescents were in feeding behavior, emotional stability and risky consumption of alcohol, indicators of life situations that need more immediate and deeper intervention.
Keywords: Screening; teenage behavior; risk factors; family relations; feeding behavior